KEY TRENDS IN THE RESTORATION OF ARCHITECTURAL HERITAGE SITES FOR MUSEUM PURPOSES IN UKRAINE - Kryzhanovskyi, Volodymyr (Theory and practice of design, 2025)
This study examines the general aspects of restoring museum and exhibition sites in Ukraine, using six architectural heritage sites as case studies. The methods of reconstruction, preservation of authenticity, and integration of modern technologies are analysed. Particular attention is given to the adaptation of historical buildings to meet museum needs. The research identifies key trends in restoration practices and outlines the challenges related to inclusivity and sustainable cultural heritage development. Purpose. The study aims to determine the key trends in the effective restoration of museum buildings in Ukraine by analysing case studies of architectural heritage restoration, literary sources, and academic publications. Methodology. The research is based on the analysis of academic and technical publications, historical sources, and practical restoration examples. A comparative method was employed to assess effective approaches to museum site restoration, allowing for the identification of patterns and key factors contributing to successful restoration. The results. The study establishes that restoration effectiveness depends on the combination of traditional methods with modern technologies and innovative construction materials. Optimal approaches to preserving architectural heritage sites have been identified, taking into account technical, historical, and cultural aspects. Scientific novelty. The research refines the understanding of how traditional restoration approaches can be combined with advanced technologies to ensure the long-term preservation of architectural objects. It highlights the importance of integrating modern technologies with traditional restoration methods to achieve longterm sustainability and authenticity preservation. Practical relevance. The findings can be used to develop methodological guidelines for the restoration and adaptation of museum and exhibition sites. The proposed principles can be applied to restoration projects in Ukraine, contributing to the preservation of cultural identity while integrating modern functional solutions.